2018
DOI: 10.1001/jama.2018.6129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recombinant Human Pentraxin 2 vs Placebo on Change in Forced Vital Capacity in Patients With Idiopathic Pulmonary Fibrosis

Abstract: clinicaltrials.gov Identifier: NCT02550873.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
163
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 198 publications
(168 citation statements)
references
References 24 publications
3
163
1
1
Order By: Relevance
“…Studies investigating effectiveness of pirfenidone in AE-IPF and studies investigating its synergistic effect with novel compounds that entered the pipeline of clinical trials (i.e. pamrevlumab and pentraxin) are greatly anticipated [29][30][31] and will hopefully transform the therapeutic management of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating effectiveness of pirfenidone in AE-IPF and studies investigating its synergistic effect with novel compounds that entered the pipeline of clinical trials (i.e. pamrevlumab and pentraxin) are greatly anticipated [29][30][31] and will hopefully transform the therapeutic management of patients.…”
Section: Discussionmentioning
confidence: 99%
“…We helped form a company called Promedior to pursue this. Promedior found that SAP is an effective therapeutic in 20 different fibrosis models, and SAP showed better efficacy and fewer side effects than current therapeutics in a Phase 1B trial and a 117-patient Phase 2 trial for pulmonary fibrosis, and a Phase 2 trial for myelofibrosis, a bone marrow fibrosis (Dillingh et al, 2013, Raghu et al, 2018. If SAP continues to be effective in further clinical trials, it would be very helpful for fibrosis patients and an example of taking Dictyostelium secreted factor research into the clinic.…”
Section: Development Of Potential Therapeutics Based On Dictyosteliummentioning
confidence: 99%
“…These brilliant results raised the hope for finding a definitive cure for IPF and paved the way for newer studies exploring the effectiveness of different molecules. Some of them, such as human recombinant pentraxin 2, PBI‐4050 and GLPG1690, showed promising results in phase 2 studies. Currently, the research landscape is highly flourishing.…”
Section: Disclosure Statementmentioning
confidence: 99%